Desenvolvimento de métodos analíticos qualitativos para a análise de darunavir comprimidos - Carolina Kogawa, Ana [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2013)
Darunavir is a protease inhibitor used in the treatment of HIV infection. It is a pillar of the drug cocktail for patients diagnosed with the virus. Quality control in the pharmaceutical industry, to verify the content of active substance and study the physicochemical characteristics of the drug, is essential to ensure final product quality. Until now, standardized methods for the analysis of darunavir have not been available in official compendia. This justifies new research, to develop and validate analytical methods, as well as physicochemical and pharmaceutical analysis for this drug, both as a raw material and a finished product. Thus, in this study, (a) the average weight of darunavir tablets and (b) the melting point of the pure drug were determined, and the following analytical techniques were performed: (c) thin-layer chromatography, (d) ultraviolet spectroscopy, (e) infrared spectroscopy and (f) high performance liquid chromatography. By developing the above techniques, it is possible to make a qualitative assessment of the quality of darunavir tablets.

O darunavir é um inibidor de protease utilizado para o tratamento da infecção pelo HIV. Trata-se de um dos pilares da terapia de coquetel para pacientes portadores do vírus. O controle de qualidade na indústria farmacêutica, para identificação do teor de substância ativa e estudo das características físico-químicas do fármaco, é de fundamental importância para garantir a qualidade do produto final. O darunavir, até então, não possui métodos de análise padronizados em compêndios oficiais. Este fato justifica novas pesquisas nesta área para o desenvolvimento e validação de métodos analíticos, bem como a análise químico-farmacêutica para este fármaco tanto na matéria-prima como no produto acabado. Dessa forma, neste trabalho foram realizados (a) peso médio; (b) determinação do ponto de fusão; (c) cromatografia em camada delgada; (d) análise na região do ultravioleta; (e) análise na região do infravermelho e (f) cromatografia líquida de alta eficiência. Através do desenvolvimento das técnicas propostas é possível avaliar qualitativamente a qualidade de darunavir em comprimidos. Palavras-chave: Análise qualitativa. Comprimidos. Controle de qualidade. Darunavir.
Development of qualitative analytical methods for monitoring darunavir tablets
Keywords: Darunavir; Qualitative analysis; Quality control; Tablets; darunavir; analytic method; drug quality; high performance liquid chromatography; infrared spectroscopy; melting point; physical chemistry; qualitative analysis; quality control; tablet property; thin layer chromatography; ultraviolet spectroscopy